Managerial and Educational Features of a Turkish University in Central Asia - L. Gagbansua; I. Keles (University of Sofia, 2007)
Newly independent states occur after the collapse of Soviet Union. A number of Turkish Higher Education Institutes were opened in Central Asia after this event. One of them is the International Ataturk Alatoo University. The International Ataturk Alatoo University is one of the first private universities established in the Kyrgyz Republic that started its educational activity in 1996. International Ataturk Alatoo University aims at being the best model for higher education depending on the highest education standards and norms in newly reshaping Central Asia. The International Atatürk Alatoo University has an education mentality motivating free thinking and personal skills in a world in which paradigms are rapidly changing. In this paper, in order to find the answer for 'what makes International Atatürk Alatoo University different from other institutes'; the strategies and features of International Atatürk Alatoo University were examined from the managerial and educational perspectives, interviews were made with students, lecturers and businessmen. Opinions of those people who have different University experiences (one International Atatürk Alatoo University experience and one local or International) were collected and discussed. By this way success factors and problems faced in the region were explained.